2015
DOI: 10.1080/2150704x.2015.1019015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of support vector machine, artificial neural network, and spectral angle mapper algorithms for crop classification using LISS IV data

Abstract: The Resourcesat-2 is a highly suitable satellite for crop classification studies with its improved features and capabilities. Data from one of its sensors, the linear imaging and self-scanning (LISS IV), which has a spatial resolution of 5.8 m, was used to compare the relative accuracies achieved by support vector machine (SVM), artificial neural network (ANN), and spectral angle mapper (SAM) algorithms for the classification of various crops and non-crop covering a part of Varanasi district, Uttar Pradesh, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(44 citation statements)
references
References 24 publications
(29 reference statements)
1
35
0
1
Order By: Relevance
“…The highest overall accuracy found in SVM and ANN algorithms was 93.45% and 92.32%, respectively. Likewise, the SAM method has low accuracy among the classification methods (74.99%) (Kumar et al, 2015). In this study, MDiP and MiD methods demonstrated potential for identifying and mapping MSAV with WV2 multispectral high-spatial resolution (MHSR) satellite imagery.…”
Section: Discussionmentioning
confidence: 98%
“…The highest overall accuracy found in SVM and ANN algorithms was 93.45% and 92.32%, respectively. Likewise, the SAM method has low accuracy among the classification methods (74.99%) (Kumar et al, 2015). In this study, MDiP and MiD methods demonstrated potential for identifying and mapping MSAV with WV2 multispectral high-spatial resolution (MHSR) satellite imagery.…”
Section: Discussionmentioning
confidence: 98%
“…The availability of high resolution Indian remote sensing satellite data from Resourcesat-2 LISS IV is expected to have a considerable effect on LULC classification accuracy. In some studies LISS IV data have been used for classification of crops and other land cover features [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The ANN classifier, a more sophisticated and robust classifier of image classification has been employed in the classification applications [3], [6]- [9]. Some researchers have used the back propagation algorithm for crop classification and estimation of crop variables in Varanasi [10]- [11]. However, so many studies have reported some problems during use of back propagation ANN for crop classification and other land cover features [3], [12].…”
Section: Introductionmentioning
confidence: 99%